2003
DOI: 10.1097/00003246-200301000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Early indicators of prolonged intensive care unit stay: Impact of illness severity, physician staffing, and pre–intensive care unit length of stay

Abstract: Patients with high WHD, and thus high costs, can be identified early. Severity of illness only partially explains high WHD. Age is less important as a predictor of high WHD than presence of infection or ventilator dependency at 24 hrs. Both long ward stays before ICU admission and lack of full-time ICU physician involvement in care increase the probability of long ICU stays. These latter two factors are potentially modifiable and deserve prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
113
3
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(144 citation statements)
references
References 42 publications
14
113
3
11
Order By: Relevance
“…We identified that higher severity of illness, shock, and BSI were independently associated with a prolonged ICU admission and that cardiovascular surgery was associated with a lower risk among all patients admitted to ICUs in our population. Several other studies 7,10,11 have investigated factors associated with prolonged admission to the ICU. Most notably, Higgins et al 7 conducted a multicentered study in 34 ICUs and found that higher severity of disease, middle age, infection, ventilation, male gender, emergency surgery, trauma, critical care fellows, and longer pre-ICU lengths of hospital stay were associated with longer ICU stays, and that the presence of full-time ICU physicians, do-not-resuscitate orders, and coma were associated with shorter admissions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified that higher severity of illness, shock, and BSI were independently associated with a prolonged ICU admission and that cardiovascular surgery was associated with a lower risk among all patients admitted to ICUs in our population. Several other studies 7,10,11 have investigated factors associated with prolonged admission to the ICU. Most notably, Higgins et al 7 conducted a multicentered study in 34 ICUs and found that higher severity of disease, middle age, infection, ventilation, male gender, emergency surgery, trauma, critical care fellows, and longer pre-ICU lengths of hospital stay were associated with longer ICU stays, and that the presence of full-time ICU physicians, do-not-resuscitate orders, and coma were associated with shorter admissions.…”
Section: Discussionmentioning
confidence: 99%
“…A second important aspect of our study is that it represents one of the largest studies to date investigating the epidemiology of prolonged ICU admission. Only two other studies 6,7 have included larger cohorts of patients. A final important strength of our study is that we assessed long-term outcome with follow-up for at least 1 year in all patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies are limited because of concerns about secular trends in outcomes, ability to control for confounding variables, and generalizability of single-center studies. Relatively few studies using large cohorts of patients with well-defined critical illness syndromes have explored this question (18)(19)(20)(21)(22).…”
mentioning
confidence: 99%